2017
DOI: 10.1039/c7dt03278a
|View full text |Cite
|
Sign up to set email alerts
|

The design of synthetic superoxide dismutase mimetics: seven-coordinate water soluble manganese(ii) and iron(ii) complexes and their superoxide dismutase-like activity studies

Abstract: Bio-inspired manganese [Mn(NPy)(HO)(CHOH)](ClO) (1) and iron [Fe(NPy)(HO)(ClO)]ClO (2) complexes derived from a pentadentate ligand (NPy = 2,6-bis((E)-1-phenyl-2-(pyridin-2-ylmethylene)hydrazinyl)pyridine) framework containing a N binding motif were synthesized and characterized using different spectroscopic methods. The molecular structures of complexes 1 and 2 were determined by X-ray crystallography. These complexes were found to be stable under physiological conditions and exhibited an excellent superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The ligand (PyPhime‐Cina) was synthesized by the reaction between 2,6‐bis(1‐phenyl hydrazinyl) pyridine [ 22 ] and cinnamaldehyde in 1:2 molar ratio. In UV‐visible spectral studies, (PyPhime‐Cina) showed strong absorption at 368 nm due to π‐π* transition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligand (PyPhime‐Cina) was synthesized by the reaction between 2,6‐bis(1‐phenyl hydrazinyl) pyridine [ 22 ] and cinnamaldehyde in 1:2 molar ratio. In UV‐visible spectral studies, (PyPhime‐Cina) showed strong absorption at 368 nm due to π‐π* transition.…”
Section: Resultsmentioning
confidence: 99%
“…In UV‐visible spectral studies, (PyPhime‐Cina) showed strong absorption at 368 nm due to π‐π* transition. [ 23 ] In IR spectral studies peak at 1,570 cm −1[ 22–24 ] clearly indicated azomethine bond formation (shown in Figure S1). The 1 H and 13 C NMR spectra were recorded in CDCl 3 and deposited in Supporting Information Figures S2 and S3.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 A number of these low molecular SOD mimetics are complexes of polyamine ligands of either cyclic or acyclic topology. [15][16][17][18][19][20] In this respect, we have recently reported that several mononuclear or binuclear manganese and copper complexes of aza-macrocyclic ligands have SOD activities in vitro which rank among the highest ones so far reported for synthetic systems. [21][22][23] A plausible way of increasing SOD activity might be the attachment of the molecules to the surface of appropriate nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%
“…7 Indeed, some Mn(III)-porphyrin (for example AEOL10150), Mn(III)salen (for example EUK-113) and seven-coordinated Mn(II)-macrocyclic polyamine complexes (for example M40403) have entered clinical tests. [8][9][10][11][12] Although Mn-polyamine complexes show very high SOD-mimetic activity, 13 certain Mn-porphyrin and Mn-salen complexes exhibit dual SOD and CAT activity. [14][15][16][17] Additional functions of manganese complexes are known such as oxidation, [18][19][20] reduction, 21 or sulfur-oxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, catalase biomimetics include single-site Mn complexes, often showing both SOD and CAT activity, which can be used as artificial small molecule catalysts for ROS detoxification and are promising as therapeutics . Indeed, some Mn­(III)-porphyrin (for example, AEOL10150), Mn­(III)-salen (for example EUK-113) and seven-coordinated Mn­(II)-macrocyclic polyamine complexes (for example M40403) have entered clinical tests. Although Mn-polyamine complexes show very high SOD-mimetic activity, certain Mn-porphyrin and Mn-salen complexes exhibit dual SOD and CAT activity. Additional functions of manganese complexes are known such as oxidation, reduction, or sulfur–oxygenation …”
Section: Introductionmentioning
confidence: 99%